5
$\begingroup$

Let $a$, $b$ and $c$ be non-negative numbers such that $ab+ac+bc\neq0$. Prove that: $$ \dfrac{1}{\sqrt{2a^2+5ab+2b^2}}+\dfrac{1}{\sqrt{2b^2+5bc+2c^2}}+\dfrac{1}{\sqrt{2c^2+5ca+2a^2}} \geq\sqrt{\frac{3}{ab+ac+bc}}.$$

I solved this problem by Holder: $$\left(\sum_{cyc}\dfrac{1}{\sqrt{2a^2+5ab+2b^2}}\right)^2\sum_{cyc}\frac{(a+b)^3}{(2a^2+5ab+2b^2)^2}\geq\left(\sum_{cyc}\frac{a+b}{2a^2+5ab+2b^2}\right)^3$$ and it remains to prove that $$(ab+ac+bc)\left(\sum_{cyc}\frac{a+b}{2a^2+5ab+2b^2}\right)^3\geq3\sum_{cyc}\frac{(a+b)^3}{(2a^2+5ab+2b^2)^2},$$ which is true by BW and by using computer.

In this topic https://artofproblemsolving.com/community/c6h542992 there is a proof (from gxggs), but it's very very complicated.

I found another way, a smooth enough, but it's still a very hard solution.

I am looking for a nice proof by hand, for which there is a possibility to find this proof during a competition.

Thank you!

$\endgroup$
2
  • 2
    $\begingroup$ Happy to see you back, Michael. $\endgroup$
    – Jean Marie
    Sep 12 at 11:58
  • $\begingroup$ Side note: Better to just stick to positive numbers? EG You need $ab\neq0$. $\endgroup$
    – Calvin Lin
    Sep 12 at 14:45
3
$\begingroup$

Remark: I give a proof using the so-called isolated fudging.

It suffices to prove that $$\frac{\sqrt{\frac{ab + bc + ca}{3}}}{\sqrt{2a^2 + 5ab + 2b^2}}\ge \frac{8c^2 + 9(a + b)c + 8ab}{8(a^2 + b^2 + c^2) + 26(ab + bc + ca)}. \tag{1}$$ Note: Taking cyclic sum on (1), we get the desired inequality.

If $c = 0$, it is easy.

If $c > 0$, WLOG, assume that $c = 1$. Let $p = a + b, ~ q = ab$. Then $0 \le q \le p^2/4$. It suffices to prove that $$\frac{\sqrt{(q + p)/3}}{\sqrt{2(p^2 - 2q) + 5q}} \ge \frac{8 + 9p + 8q}{8(p^2 - 2q + 1) + 26(q + p)}.$$ Squaring both sides, it suffices to prove that \begin{align*} &-92\,{q}^{3}+ \left( -224\,{p}^{2}+188\,p-224 \right) {q}^{2}+ \left( 64\,{p}^{4}-288\,{p}^{3}+313\,{p}^{2}+144\,p-128 \right) q \\ &\quad +64\,{p}^{5} -70\,{p}^{4}-60\,{p}^{3}+32\,{p}^{2}+64\,p \ge 0. \end{align*} Denote LHS by $f(q)$. We have $f''(q) = - 448p^2 + 376p - 448 - 552q$. So, we have $f''(q) < 0$ on $q \ge 0$. So, $f(q)$ is concave on $q \ge 0$. Also, we have $f(0) = 64p^5 - 70p^4 - 60p^3 + 32p^2 + 64p \ge 0$ and $f(p^2/4) = \frac{1}{16}\,p \left( 9\,{p}^{3}+96\,{p}^{2}+256\,p+256 \right) \left( p-2 \right) ^{2} \ge 0$. Thus, $f(q) \ge 0$ for all $q\in [0, p^2/4]$.

We are done.

$\endgroup$
8
  • $\begingroup$ Thank you! I have found a very easy proof by $uvw$. $\endgroup$ Sep 13 at 2:03
  • $\begingroup$ @MichaelRozenberg Nice. uvw is very powerful. $\endgroup$
    – River Li
    Sep 13 at 2:09
  • $\begingroup$ I have seen this technique a few times now and wondering if you have a general technique to find the lower bounds that sum up to $1.$ $\endgroup$
    – dezdichado
    Sep 13 at 2:33
  • 1
    $\begingroup$ @dezdichado If quadratic fraction actually work i.e. $ f(a,b,c)\ge\frac{p_1a^2+p_2b^2+p_3c^2+p_4ab+p_5bc+p_6ca}{a^2+b^2+c^2+q(ab+bc+ca)}$, we need to find the coefficients which satisfies such as $f(a_0, b_0, c_0)$ ($a_0, b_0, c_0$ is the equality case for the inequality $f(a,b,c) + f(b,c,a) + f(c,a,b) \ge 1$, also the stationary condition $f'(a_0, b_0, c_0) = 0$, also sum to 1. $\endgroup$
    – River Li
    Sep 13 at 3:09
  • $\begingroup$ @dezdichado If $f(a, b, c)$ is symmetric about $a, b$, we can simplify something such as in this proof, $p_1 = p_2$, $p_5 = p_6$, etc. $\endgroup$
    – River Li
    Sep 13 at 3:11
1
$\begingroup$

I found the following solution.

We need to prove that: $$\sum_{cyc}\left(\frac{1}{\sqrt{2a^2+5ab+2b^2}}-\frac{1}{\sqrt{3(ab+ac+bc)}}\right)\geq0$$ or $$\sum_{cyc}\frac{3ac+3bc-2a^2-2b^2-2ab}{2a^2+5ab+2b^2+\sqrt{3(ab+ac+bc)(2a^2+5ab+2b^2)}}\geq0$$ or $$\sum_{cyc}\frac{(c-a)(2a+b)-(b-c)(2b+a)}{2a^2+5ab+2b^2+\sqrt{3(ab+ac+bc)(2a^2+5ab+2b^2)}}\geq0$$ or $$\sum_{cyc}(a-b)\left(\tfrac{2b+c}{2b^2+5bc+2c^2+\sqrt{3(ab+ac+bc)(2b^2+5bc+2c^2)}}-\tfrac{2a+c}{2a^2+5ac+2c^2+\sqrt{3(ab+ac+bc)(2a^2+5ac+2c^2)}}\right)\geq0$$ or $$\sum_{cyc}(a-b)^2\left((2a+c)(2b+c)-\tfrac{3c\sqrt{3(ab+ac+bc)(2a+c)(2b+c)}}{\sqrt{(a+2c)(2b+c)}+\sqrt{(2a+c)(b+2c)}}\right)\left(2a^2+5ab+2b^2+\sqrt{3(ab+ac+bc)(2a^2+5ab+2b^2)}\right)\geq0.$$ Now, let $a\geq b\geq c$.

Thus, since $$(2a+c)(2b+c)-\tfrac{3c\sqrt{3(ab+ac+bc)(2a+c)(2b+c)}}{\sqrt{(a+2c)(2b+c)}+\sqrt{(2a+c)(b+2c)}}\geq0,$$ $$(2a+b)(2c+b)-\tfrac{3b\sqrt{3(ab+ac+bc)(2a+b)(2c+b)}}{\sqrt{(a+2b)(2c+b)}+\sqrt{(2a+b)(c+2b)}}\geq0$$ and $$b(a-c)\geq a(b-c),$$ it remains to prove that: $$a^2\left((2a+b)(2c+b)-\tfrac{3b\sqrt{3(ab+ac+bc)(2a+b)(2c+b)}}{\sqrt{(a+2b)(2c+b)}+\sqrt{(2a+b)(c+2b)}}\right)\left(2a^2+5ac+2c^2+\sqrt{3(ab+ac+bc)(2a^2+5ac+2c^2)}\right)+$$ $$+b^2\left((2b+a)(2c+a)-\tfrac{3a\sqrt{3(ab+ac+bc)(2b+a)(2c+a)}}{\sqrt{(b+2a)(2c+a)}+\sqrt{(2a+b)(c+2a)}}\right)\left(2b^2+5bc+2c^2+\sqrt{3(ab+ac+bc)(2b^2+5bc+2c^2)}\right)\geq0.$$ But $$2a^2+5ac+2c^2+\sqrt{3(ab+ac+bc)(2a^2+5ac+2c^2)}\geq2b^2+5bc+2c^2+\sqrt{3(ab+ac+bc)(2b^2+5bc+2c^2)},$$ $$\sqrt{(a+2b)(2c+b)}+\sqrt{(2a+b)(c+2b)}=\sqrt{4b^2+5ab+4ac+5bc+2\sqrt{(2a^2+5ab+2b^2)(2c^2+5bc+2b^2)}}\geq$$ $$\geq\sqrt{4b^2+4ab+4ac+4bc+2\sqrt{(2a^2+4ab+2b^2)(2c^2+4bc+2b^2)}}=$$ $$=\sqrt{8(a+b)(b+c)}$$ and similarly $$\sqrt{(b+2a)(2c+a)}+\sqrt{(2a+b)(c+2a)}\geq\sqrt{8(a+b)(a+c)}.$$ Thus, it's enough to prove that: $$a^2(2a+b)(2c+b)+b^2(2b+a)(2c+a)\geq\tfrac{3ab\sqrt{3(ab+ac+bc)}}{\sqrt{8(a+b)}}\left(a\sqrt{\tfrac{2a+b)(2c+b)}{b+c}}+b\sqrt{\tfrac{(2b+a)(2c+a)}{a+c}}\right).$$ Now, by C-S $$a\sqrt{\tfrac{2a+b)(2c+b)}{b+c}}+b\sqrt{\tfrac{(2b+a)(2c+a)}{a+c}}\leq\sqrt{(a+b)\left(\tfrac{a(2a+b)(2c+b)}{b+c}+\tfrac{b(2b+a)(2c+a)}{a+c}\right)}\leq$$ $$\leq\sqrt{(a+b)\left(\tfrac{a(2a+b)\frac{3}{2}(c+b)}{b+c}+\tfrac{b(2b+a)\frac{3}{2}(c+a)}{a+c}\right)}=\sqrt{3(a+b)(a^2+ab+b^2)}.$$ Id est, it's enough to prove that: $$8\left(a^2(2a+b)(2c+b)+b^2(2b+a)(2c+a)\right)^2\geq81a^2b^2(ab+ac+bc)(a^2+ab+b^2),$$ which is true because $$8\left(a^2(2a+b)(2c+b)+b^2(2b+a)(2c+a)\right)^2=$$ $$=8\left(2a^2b^2+2a^3b+2ab^3+2a^2bc+2b^2ac+4a^3c+4b^3c\right)^2\geq$$ $$\geq8\left(2a^2b^2+2a^3b+2ab^3+2a^2bc+2b^2ac+4a^2bc+4b^2ac\right)^2=$$ $$=32a^2b^2(a^2+ab+b^2+3ac+3bc)^2\geq$$ $$\geq32a^2b^2((a^2+ab+b^2)^2+6(a^2+ab+b^2)(ac+bc))=$$ $$=32a^2b^2(a^2+ab+b^2)(a^2+ab+b^2+6(ac+bc))\geq$$ $$\geq32a^2b^2(a^2+ab+b^2)(3ab+3(ac+bc))=$$ $$=96a^2b^2(a^2+ab+b^2)(ab+ac+bc)\geq$$ $$\geq81a^2b^2(a^2+ab+b^2)(ab+ac+bc)$$ and we are done!


I think, the best way it's the following.

By the gxggs's idea (see here https://artofproblemsolving.com/community/c6h542992p3142759 ) it's enough to prove that $$\sum_{cyc}{\frac{12(a+b)}{17a^2+38ab+17b^2}}\geq \sqrt{\frac{3}{ab+bc+ca}}.$$ Now, let $a+b+c=3u$, $ab+ac+bc=3v^2$ and $abc=w^3$.

Thus, since for $(a,b,c)=(1,\zeta,\zeta^2)$, where $\zeta^2+\zeta+1=0$, we have $w^3\neq0$, $$u=v^2=a^2+ab+b^2=a^2+ac+c^2=b^2+bc+c^2=0$$ and $$\prod_{cyc}(17a^2+38ab+17b^2)=21^3w^6,$$ we need to prove that $f(w^3)\geq0,$ where $f$ is a concave function,

which by $uvw$ (about $uvw$ see here: https://artofproblemsolving.com/community/c6h278791 ) says that it's enough to prove $$\sum_{cyc}{\frac{12(a+b)}{17a^2+38ab+17b^2}}\geq \sqrt{\frac{3}{ab+bc+ca}}$$ in the following cases.

  1. Two variables are equal (it's enough to assume $b=c=1$);

  2. $w^3=0$ (it's enough to assume $c=0$ and $b=1$),

which easy to check.

$\endgroup$
1
  • 1
    $\begingroup$ You may separate two parts using <hr> before "I think, the best way it's the following." Or, move the uvw solution to another one. $\endgroup$
    – River Li
    Sep 18 at 2:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.